Given quadratic equation is px (x – 2) + 6 = 0

⇒ px^{2} − 2px + 6 = 0 … (1)

By comparing equation (1)with ax^{2} + bx + c = 0,

we get a = p, b = −2p and c = 6.

Since given that the given quadratic equation has equal roots.

∴ D = b^{2}– 4ac = 0 (∵ for equal roots D = 0)

⇒(−2p)^{2} − 4 × p × 6 = 0

⇒ 4p^{2} − 24p = 0

⇒ 4p (p – 6) = 0

⇒ p = 0 or p – 6 = 0

⇒ p = 0 or p = 6 but p ≠ 0

(∵ If p = 0 then given equation is not quadratic equation)

**Hence the value of p is 6, for which the given quadratic equation have equal roots.**